Blood-Flow Restricted Warm-Up Alters Muscle Hemodynamics and Oxygenation during Repeated Sprints in American Football Players - Jean-François Fortin; François Billaut (MDPI AG, 2019)
Team-sport athletes and coaches use varied strategies to enhance repeated-sprint ability (RSA). Aside from physical training, a well-conducted warm-up enhances RSA via increased oxidative metabolism. Strategies that impede blood flow could potentiate the effects of a warm-up due to their effects on the endothelial and metabolic functions. This study investigated whether performing a warm-up combined with blood-flow restriction (WFR) induces ergogenic changes in blood volume, muscle oxygenation, and RSA. In a pair-matched, single-blind, pre-post parallel group design, 15 American football players completed an RSA test (12 × 20 m, 20 s rest), preceded by WFR or a regular warm-up (SHAM). Pressure was applied on the athletes’ upper thighs for ≈15 min using elastic bands. Both legs were wrapped at a perceived pressure of 7 and 3 out of 10 in WFR and SHAM, respectively. Changes in gastrocnemius muscle oxygen saturation (SmO2) and total hemoglobin concentration ([THb]) were monitored with near-infrared spectroscopy. Cohen’s effect sizes (ES) were used to estimate the impact of WFR. WFR did not clearly alter best sprint time (ES −0.25), average speed (ES 0.25), total time (ES −0.12), and percent decrement score (ES 0.39). While WFR did not meaningfully alter average SmO2 and [THb], the intervention clearly increased the maximum [THb] and the minimum and maximum SmO2 during some of the 12 sprint/recovery periods (ES 0.34−1.43). Results indicate that WFR positively alters skeletal muscle hemodynamics during an RSA test. These physiological changes did not improve short-term RSA, but could be beneficial to players during longer activities such as games.